2020
DOI: 10.3390/molecules25122804
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Lactaptin Induces Immunogenic Cell Death and Creates an Antitumor Vaccination Effect in Vivo with Enhancement by an IDO Inhibitor

Abstract: Natural compounds of various origins are intensively investigated for their antitumor activity. Potential benefits of antitumor therapy can be achieved when cytotoxic agents kill cancer cells and these dying cancer cells drive adoptive immunity to the tumor. This strategy was successfully demonstrated for chemotherapeutic drugs that induce immunogenic type of cell death (ICD) with release of DAMPs (danger associated molecular patterns) and exposure of “eat me” signals. In this study, we demonstrated that recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Considering the enhanced PDT ability observed in vitro , it is reasonable to assume that NGs can induce the PDT effect in vivo under single NIR laser irradiation. Besides, robust PDT as well as PTT can not only directly kill tumor cells but also induce immunogenic cell death (ICD), providing antitumor immunity and long-term immunological memory [ 40 ]. In light of this scenario, the antitumor efficiency of PA imaging-guided triple therapy (enhanced-PDT, PTT, and induced antitumor immunity therapy) were investigated in LM8 tumor-bearing mice.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the enhanced PDT ability observed in vitro , it is reasonable to assume that NGs can induce the PDT effect in vivo under single NIR laser irradiation. Besides, robust PDT as well as PTT can not only directly kill tumor cells but also induce immunogenic cell death (ICD), providing antitumor immunity and long-term immunological memory [ 40 ]. In light of this scenario, the antitumor efficiency of PA imaging-guided triple therapy (enhanced-PDT, PTT, and induced antitumor immunity therapy) were investigated in LM8 tumor-bearing mice.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were prepared in according to the manufacturer’s protocols and their optical density was detected with a multichannel spectrophotometer Apollo LB912 (Berthold Technologies, TN, USA) at 450 nm (reference wavelength 620 nm). The total cellular HMGB1 was detected by Western blot as was described previously [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Serum cytokines were measured using the Multi-Analyte ELISAArray Kit MEM−004A (Qiagen, USA) where the level of IL−1α, Il−1β, IL−4, IL−6, IL−10, IL−12, IL−17α, INF- γ, TNF- α, G-CSF and GM-CSF can be assessed. Murine blood was isolated from the mice 1 h after the second CAP irradiation, and the serums were prepared as described previously [ 38 ]. Serum samples were diluted 8 times for subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant analog of lactaptin (RL2). Recent studies have shown that a recombinant analog of the human milk pro-apoptotic protein lactaptin (RL2) [ 79 , 80 ] can induce ICD in vitro by activating the whole cascade of immunogenic cell death markers and elicit an antitumor immune response in the prophylactic vaccination model [ 81 ]. Thus, in experiments on immunocompetent C3H/He mice, 43% of mice vaccinated with RL2-treated MX-7 murine rhabdomyosarcoma cells did not develop a tumor nodule after they had been re-challenged.…”
Section: Drugs Inducing Immunogenic Cell Deathmentioning
confidence: 99%
“…It is also worth mentioning that the growth rate of tumors that had actually developed was significantly lower compared to the control group. Ethyl pyruvate, an indoleamine 2,3-dioxygenase inhibitor, used in combination with cells incubated in the presence of RL2 potentiated the vaccination effect of RL2-treated cells by up to 60% [ 81 ].…”
Section: Drugs Inducing Immunogenic Cell Deathmentioning
confidence: 99%